The Role of Internal Controls in Optimizing Hospital Capacity and Staffing Efficiency - Shelar, Anand G; Puranik, Ashish M (International Journal of Engineering and Management Research, 2025)
Hospitals today encounter persistent challenges in maintaining optimal capacity and achieving staffing efficiency, all while striving to deliver high-quality healthcare services. Fluctuating patient volumes, resource constraints, and staffing shortages can significantly impact operational performance and patient outcomes. Internal control systems are crucial in addressing these challenges by promoting efficiency, ensuring regulatory compliance, and enhancing overall hospital operations. These systems provide a structured framework for monitoring processes, identifying inefficiencies, mitigating risks, and improving resource allocation. This study conducts a comprehensive analysis of hospital capacity and staffing data to uncover critical operational gaps and inefficiencies that hinder effective service delivery. Through detailed evaluation, key factors contributing to capacity bottlenecks and staffing imbalances are identified. Based on the findings, the study proposes a set of targeted internal control mechanisms aimed at strengthening hospital management practices. These recommendations include the implementation of real-time capacity monitoring systems, predictive analytics for staffing optimization, automated scheduling tools, and enhanced workforce management protocols. By integrating these internal control strategies, hospitals can improve operational efficiency, reduce staff burnout, optimize resource utilization, and ultimately enhance the quality of patient care. This research highlights the indispensable role of internal controls in fostering organizational resilience, improving healthcare outcomes, and positioning hospitals for sustainable success in an increasingly complex and dynamic healthcare environment.